2016
DOI: 10.1007/s11060-016-2135-8
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord ependymoma: a review of the literature and case series of ten patients

Abstract: Spinal cord ependymoma (SCE) is a rare tumor that is most commonly low-grade. Complete surgical resection has been established as first-line treatment and can be curative. However, SCEs tend to recur when complete tumor resection is not possible. Evidence supporting the use of adjuvant radiation and chemotherapy is not definitive. We review the most recent literature on SCE covering a comprehensive range of topics spanning the biology, presentation, clinical management, and outcomes. In addition, we present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
106
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 48 publications
2
106
0
4
Order By: Relevance
“…[15][16][17] GTR is facilitated in characteristically well-defined and encapsulated World Health Organization (WHO) Grade I tumors; however, this is less likely in infiltrative grade II and the more aggressive grade III ependymomas. 18 Whenever possible, intramedullary ependymomas should be removed en bloc, as piecemeal removal may facilitate CSF dissemination. 19 Although surgical excision of spinal ependymomas is the most important factor determining PFS and OS, it is not without risk.…”
Section: Intramedullary Spinal Cord Ependymomamentioning
confidence: 99%
“…[15][16][17] GTR is facilitated in characteristically well-defined and encapsulated World Health Organization (WHO) Grade I tumors; however, this is less likely in infiltrative grade II and the more aggressive grade III ependymomas. 18 Whenever possible, intramedullary ependymomas should be removed en bloc, as piecemeal removal may facilitate CSF dissemination. 19 Although surgical excision of spinal ependymomas is the most important factor determining PFS and OS, it is not without risk.…”
Section: Intramedullary Spinal Cord Ependymomamentioning
confidence: 99%
“…Ependymoma is a rare primary tumor of the central nervous system and can present anywhere along the ventricular system and spinal cord. Surgical intervention is usually necessary to ensure favorable neurological outcome [ 1 , 2 ]. It is known that specific types of central nervous system tumors (for instance meningiomas) can accelerate in growth during pregnancy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In adults, ependymomas are the most common ISCT, comprising approximately 50%-60% of ISCTs. 2,3 Most ependymomas are slow growing and well demarcated from the spinal cord parenchyma. 7 Accordingly, gross-total resection (GTR) is possible in most cases of ependymoma.…”
mentioning
confidence: 99%
“…Previous studies have reported that the extent of resection is a strong predictor of progression-free survival (PFS). 2,8,9 Intramedullary astrocytomas, the second most common ISCT, possess more infiltrative features than ependymomas. 7,14 Because of this infiltrative characteristic, the relationship between GTR and PFS in astrocytoma is less clear, 12 and adjuvant therapy such as radiotherapy and chemotherapy is often combined with resection.…”
mentioning
confidence: 99%